The Impact of Health Information Privacy Concerns on Engagement and Payment Behaviors in Online Health Communities - Wu, Banggang; Luo, Peng; Li, Mengqiao; Hu, Xiao (Frontiers in Psychology, 2022)
Online health communities (OHCs) have enjoyed increasing popularity in recent years, especially in the context of the COVID-19 pandemic. However, several concerns have been raised regarding the privacy of users’ personal information in OHCs. Considering that OHCs are a type of data-sharing-driven platform, it is crucial to determine whether users’ health information privacy concerns influence their behaviors in OHCs. Thus, by conducting a survey, this study explores the impact of users’ health information privacy concerns on their engagement and payment behaviors in OHCs. The empirical results show that users’ concerns about health information privacy reduce their payment behavior in OHCs by negatively influencing their OHC engagement. Further analysis reveals that if users have higher benefit appraisals (i.e., perceived informational and emotional support from OHCs) and lower threat appraisals (i.e., perceived severity and vulnerability of information disclosure from OHCs), the negative effect of health information privacy concerns on users’ OHC engagement will decrease.